SAT0482 Risk Factors for Severe Infection and Outcome of Secondary Hypogammaglobulinaemia in Patients with Autoimmune Rheumatic Diseases Treated with Rituximab: Preliminary Results from 400 Patients at A Single Centre. (15th July 2016) - Md Yusof, M.Y.; Hensor, E.M.; Das, S.; Vital, E.M.; Emery, P.; Savic, S.
Abstract : Background: Rituximab (RTX) is used in various autoimmune rheumatic diseases (AIRDs) that are refractory to standard therapies. Attrition of long-lived plasma cells and hypogammaglobulinaemia may occur with repeat cycles of therapy leading to serious infection. Objectives: To evaluate risk factors for severe infection and assess outcome of secondary hypogammaglobulinaemia during RTX treatment in AIRDs. Methods: We conducted a retrospective observational study of all patients with AIRDs treated with RTX at a single centre.Each cycle of RTX consisted of 2x1000mg infusions repeated on clinical relapse. IgM, IgA and IgG levels were measured at baseline and 6 months after each cycle. Baseline factors for association with serious infection within 12 months of a RTX cycle were tested using univariate (UVA) and multivariate (MVA) logistic regression analyses. Results: The first 400 consecutive patients from a total cohort of 800 were analysed. 254 (63%) had RA, 88 (22%) SLE, 47 (12%) AAV, 6 (1.5%) DM, 3 APS (1%) and 2 (0.5%) SSc. Total follow-up: 1650.3 patient-years. There were 166 serious infections recorded in 101 patients; 135 in 88 within 12 months of a cycle (8.1/100 patient years). Rates were lower in connective tissue disease (6.5) than RA (9.4). In MVA, previous severe infection, corticosteroids and low IgG were significantly associated with increased risk of serious infection. Ig data were available in 375 (94%) patients. At RTX initiation, 23 (6%) patients had low IgG (normal range 6–16 g/L). Following RTX treatment, 18 remained low, 3 returned to normal and 15 had developed new low IgG. 6 patients required Ig replacement due to recurrent serious infections related to low IgG. Conclusions: We have identified risk factors for serious infection at RTX initiation including previous serious infection, concomitant corticosteroids and low IgG. Most hypogammaglobulinaemia persisted with subsequent treatment thus highlighting the need for Ig monitoring. Further analysis of changes in Ig levels and infection in repeat cycles is in progress and can be used to develop guidelines for safety monitoring of rituximab. Acknowledgement: Dr John Baptiste Candelier, Lt Kol Dr Hatem and Huma Cassamoali Disclosure of Interest: M. Y. Md Yusof: None declared, E. M. Hensor: None declared, S. Das: None declared, E. M. Vital Grant/research support from: Roche, GSK, P. Emery Grant/research support from: Abbott, BMS, Pfizer, MSD and Roche., Consultant for: BMS, Abbott, Pfizer, MSD, Novartis, Roche and UCB, S. Savic: None declared